Meanings of nursing professionals' experiences in the context of the pandemic of COVID-19 - Cíntia Nasi; Priscila Maria Marcheti; Elda de Oliveira; Larissa de Almeida Rezio; Sonia Regina Zerbetto; Aline Macêdo Queiroz; Anderson Reis de Sousa; Zaira Letícia Tissot; Wanderson Carneiro Moreira; Maria do Perpétuo Socorro de Sousa Nóbrega (Rev Rene, 2021)
Objective: to understand the meanings that nursing professionals attribute to their experiences in the context of the COVID-19 pandemic. Methods: Qualitative study with 719 professionals. Data were collected virtually and processed by Interface de R pour les Analyses Multidimensionnelles de Textes et de Questionnaires. The analysis was conducted in the light of the theoretical-philosophical referential of Phenomenological Sociology. Results: four categories emerged from the discourse analysis: meanings of the experiences related to oneself; meanings of the experiences related to others; meanings of the experiences related to working conditions; and meanings of the experiences faced with the uncertainties of the future. Conclusion: the experiences are marked by suffering in relation to personal aspects, to their social networks and to the world of work itself. Strategies that support these professionals currently and in continued care in the medium and long term need to be established in order to preserve their mental health.